2009
DOI: 10.1051/0004-6361/200810978
|View full text |Cite
|
Sign up to set email alerts
|

Gravitational potential and X-ray luminosities of early-type galaxies observed with XMM-Newton and Chandra

Abstract: Aims. We study the dark matter content in early-type galaxies and investigate whether X-ray luminosities of early-type galaxies are determined by the surrounding gravitational potential. Methods. We derived gravitational mass profiles of 22 early-type galaxies observed with XMM-Newton and Chandra. Results. Sixteen galaxies show constant or decreasing radial temperature profiles, and their X-ray luminosities are consistent with kinematical energy input from stellar mass loss. The temperature profiles of the oth… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
83
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(93 citation statements)
references
References 41 publications
9
83
1
Order By: Relevance
“…More specifically, we find that inside r e the stellar component accounts for < ∼ 70% of the gravitating mass. This result is not new (see, e.g., Kronawitter et al 2000;Nagino & Matsushita 2009, where 22 objects with XMM-Newton and Chandra X-ray luminosities are mass-modeled). However, our finding is at odds with the claim of substantial proportions of DM inside r e (Humphrey et al 2006) and with the idea that the well known tilt of the fundamental plane of ellipticals is due to systematic variations of the DM fraction inside r e with galaxy properties.…”
Section: Discussionmentioning
confidence: 91%
“…More specifically, we find that inside r e the stellar component accounts for < ∼ 70% of the gravitating mass. This result is not new (see, e.g., Kronawitter et al 2000;Nagino & Matsushita 2009, where 22 objects with XMM-Newton and Chandra X-ray luminosities are mass-modeled). However, our finding is at odds with the claim of substantial proportions of DM inside r e (Humphrey et al 2006) and with the idea that the well known tilt of the fundamental plane of ellipticals is due to systematic variations of the DM fraction inside r e with galaxy properties.…”
Section: Discussionmentioning
confidence: 91%
“…This model has properties consistent with observed massive early-type (and even shell) galaxies (Auger et al 2010;Nagino & Matsushita 2009;Fukazawa et al 2006). The potential of the cannibalized galaxy is chosen to be a single Plummer sphere with the total mass M = 2 × 10 10 M and Plummer radius b * = 2 kpc.…”
Section: Parameters Of the Simulationmentioning
confidence: 92%
“…Several methods have been used to measure the gravitational potentials and their gradients of elliptical galaxies, including strong and weak gravitational lensing (e.g., Gavazzi et al 2007;Mandelbaum et al 2008;Auger et al 2010), X-ray observations of hot gas in the massive gas-rich galaxies (e.g., Fukazawa et al 2006;Nagino & Matsushita 2009;Churazov et al 2008;Das et al 2010), rotation curves of detected disks and rings of neutral hydrogen (e.g., Weijmans et al 2008), stellar-dynamical modeling from integrated light spectra (e.g., Weijmans et al 2009;de Lorenzi et al 2009;Churazov et al 2010;Thomas et al 2011), and the use of tracers such as planetary nebulae, globular clusters, and satellite galaxies (e.g., Coccato et al 2009;Nierenberg et al 2011;Deason et al 2012;Norris et al 2012). All these methods have their limits, such as the redshift of the observed object, the luminosity profile, and gas content.…”
Section: Introductionmentioning
confidence: 99%
“…For galaxies with extended gas beyond the ACIS chips, we compared our measurements with results in the literature. For example, Nagino & Matsushita (2009) recently analyzed Chandra and XMM-Newton observations for a sample of gas rich elliptical galaxies and reported their gas luminosities and temperatures in concentric annuli. We estimated the emission-weighted average temperature and confirmed that our results are consistent with those of Nagino & Matsushita within the uncertainties.…”
Section: X-ray Data Analysismentioning
confidence: 99%